2009
DOI: 10.1292/jvms.001465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bispectral Index (BIS) as an Indicator of Central Nervous System Depression in Horses Anesthetized with Propofol

Abstract: ABSTRACT. The bispectral index (BIS) was evaluated as an indicator of central nervous system (CNS) depression in horses anesthetized with propofol. Five non-premedicated horses were anesthetized with 7 mg/kg, IV propofol and the minimum infusion rate (MIR) of propofol required to maintain anesthesia was determined during intermittent positive pressure ventilation in each horse. The BIS was determined 20 min later and after stabilization at 2.0 MIR, 1.5 MIR, and 1.0 MIR. The BIS was also recorded after the cess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 37 publications
(40 reference statements)
4
26
1
2
Order By: Relevance
“…Yamashita et al [20] reported that BIS monitoring was an indicator to detect intraoperative awareness but did not show the degree of CNS depression. In this study, BIS value decreased parallel to depth of anesthesia and no reflex response was present related to anesthesia either in dogs of ISO group or PRO group during surgical procedure.…”
Section: Tablo 1 Propofol Ve Izofluran Gruplarında Kalp Frekansı Somentioning
confidence: 99%
“…Yamashita et al [20] reported that BIS monitoring was an indicator to detect intraoperative awareness but did not show the degree of CNS depression. In this study, BIS value decreased parallel to depth of anesthesia and no reflex response was present related to anesthesia either in dogs of ISO group or PRO group during surgical procedure.…”
Section: Tablo 1 Propofol Ve Izofluran Gruplarında Kalp Frekansı Somentioning
confidence: 99%
“…However, there are studies in which BIS is used as the target variable for closed-loop control of hypnotic drugs' administration. 60,61 Regarding animals, the application of BIS during general anaesthesia has been investigated in a diversity of species including studies of BIS monitoring in horses, 62,63 pigs, 27,64 -67 In dogs, an inverse relationship between BIS values and multiples of isoflurane 72 and sevoflurane 71 was found. In pigs, a correlation between isoflurane and BIS was found, although no correlation was found between a numerical clinical scale and the values of BIS.…”
Section: Human Anaesthesia Commercial Monitors Bispectral Indexmentioning
confidence: 99%
“…In animals, it is difficult to use adhesive electrodes without shaving the head skin. Subdermal needle electrodes have been adopted especially in dogs, 72,96 horses 63,97,98 and cats. 76 Subdermal needle electrodes have the advantage of dispensing with clipping the head fur, which is important in the case of companion and racing animals where appearance of the animal is important and also the fact that the conducting electrode tip is bathed directly in tissue fluid, improving the interface between the generator and recording system.…”
Section: Ioc-view Monitormentioning
confidence: 99%
“…It is also reported that the BIS correctly predicts the degree of CNS depression associated with isoflurane-induced anesthesia [4, 12, 18]. On the other hand, the BIS has been reported as an unreliable indicator of anesthetic depth during propofol or isoflurane anesthesia in horses [6, 19]. Others report that BIS indicates hypnosis levels but does not predict intraoperative movement during halothane and sevoflurane anesthesia in horses [1].…”
mentioning
confidence: 99%
“…Based on a previous report, BIS values were measured using subdermal spiral needle electrodes (TN204-035, Unique Medical Co., Ltd., Tokyo, Japan) in all horses [19]. These electrodes were placed on the frontal and temporal cephalic regions and connected to a BIS monitor (A-3000, Aspect Medical Systems, Natick, MA, U.S.A.).…”
mentioning
confidence: 99%